ASSOCIATION BETWEEN CRANIOVERTEBRAL ANGLE AND THE RISK OF FALLS AMONG COMMUNITY-DWELLING OLDER ADULTS IN SELECTED COMMUNITIES IN OYO STATE, NIGERIA (Journal of Biomedical Investigation, 2024)
Background: Reduced craniovertebral angle (< 490 ) i.e. forward head posture is the most common type of postural abnormality seen in older adults which result from displacement of the vertical line of the body’s centre of gravity.Aim: This study was designed to determine the association between the craniovertebral angle (head posture) and risk of falls of community dwelling older adults in Oyo state.Materials and Methods: This was a cross-sectional study in which consecutive sampling was used to recruit 195 participants (97 females, 98 males). Universal goniometer and adapted Time-up-and-go test were used to measure the participant’s craniovertebral angle (CVA) and risk of fall respectively. Chi square test was used to determine the level of association between variables while Mann Whitney U test was used to determine the difference between the two age groups. Alpha level was set at < 0.05.Results: The mean CVA of the participants was 36.10±6.80 degrees with 186 (95.40%) participants having CVA
Keywords: Craniovertebral angle; risk of fall; community-dwelling; older adults